Terms Used to Describe Abnormalities of Joint Kinematics: An Overview - Jagar Omar Doski (مجلة الكوفة الطبية)
Background: In the joints, the movements, active or passive, occur normally in certain physiological planes: axes or directions, and within certain limits. In certain pathologies, the joint kinematics may be affected in one of the following ways: limitation of the normal movements, movement beyond the normal limits, or movement in the non-physiological planes. Different terms were used to describe the abnormalities of the joint kinematics. Nowadays, terms like joint hypermobility, joint laxity, joint instability, and ligamentous laxity are, synonymously or not, still used in some literature in their correct place. The current article aimed to review the abnormalities of joint kinematics and the new concepts of optimum application of the terms used to describe them. It has reached to some conclusions like: limitation of joint movement is the term used to describe any incomplete joint movement within a physiological plane and standard limits; Joint hypermobility is the term used to describe the ability to do a joint movement in a physiological plane but beyond the usual limits. Joint instability is the term used to describe the liability of a joint to move in non-physiological planes.